Réponses

  • Utilisateur Brainly
2014-09-24T18:18:08+02:00
E= (x + 1)² + 7x(2 - x)
E= x² + 2x + 1 + 14x - 7x²
E= - 6x² + 16x + 1

F= (x + 3)(2x + 1) - 3x(2x + 5)
F= 2x² + x + 6x + 3 - 6x² - 15x
F= - 4x² - 8x + 3

G= (4t + 1)(4t - 1) - (3t + 2)²
G= 16t² - 1 - (9t² + 12t + 4)
G= 16t² - 1 - 9t² - 12t - 4
G= 4t² - 12t - 5

H= 2(s + 5)(s - 5) + (4s + 3)²
H= 2(s² - 25) + 16s² + 24s + 9
H= 2s² - 50 + 16s² + 24s + 9
H= 18s² + 24s - 41

I= (3x + 4)² - (1 - 2x)(6 + x)
I= 9x² + 24x + 16 - (6 + x - 12x - 2x²)
I= 9x² + 24x + 16 - 6 - x + 12x + 2x²
I= 11x² + 35x + 10